The Solution to the Financial Literacy Problem: What is the Answer? - Sharon M Taylor; Suzanne Wagland (Australasian Accounting, Business and Finance Journal, 2013)
Over the last two decades the need for a financially literate population has grown in importance. Hence in Australia, it is imperative that individuals possess both the financial knowledge and capability to make sound financial decisions. In contrast, the results of the Australian & New Zealand Bank (ANZ) surveys from 2003 to 2010 have demonstrated that there is a substantial deficiency in the level of financial literacy amongst many of the Australian population. Both the government and the private sector have encouraged the development of financial education programs as an important tool in remedying the detected low levels of financial literacy as reported in the ANZ research. The Australian Security and Investment Commission (ASIC), the government regulator, has strongly promoted the need to develop confident and informed consumers and investors through the provision of quality financial education. ASIC’s focus was reiterated in its Report 229, the National Financial Literacy Strategy. This report which was announced in March 2011 set out the strategy for the development and delivery of initiatives to improve financial literacy levels in Australia (ASIC 2011). In particular, the National Strategy has been developed to improve the level of financial literacy among Australian students. The focus is on incorporating financial education through the existing school curriculum, beginning in kindergarten through to year 12 students. The aim of this research paper is to challenge and ask questions relating to the Australian Government’s financial literacy strategy directed at schools. This direction would appear to have limited support of success, given the evidence published in the USA, and to a limited extent in the United Kingdom and Europe. This study reviews the current evidence available in both Australia and the USA in relation to financial literacy projects in schools. In respect of the international experience this paper explores the possible reasons for their limited success, and in some cases failure, to deliver the desired outcomes. In Australia there has been no academic research as to the possible effectiveness of teaching financial literacy at a school level. Given the USA research into such initiatives, this paper seeks to question the policy direction of the government in Australia. This paper also challenges the validity of the current Australian approach. The emphasis placed upon school financial literacy programs defies the wealth of evidence overseas which has failed to identify any measurable improvement in financial knowledge, attitudes and behaviour as a result of embedding financial literacy in school education curriculum.
Keywords: Financial literacy; ageing population; government policy; education